2020
DOI: 10.2174/1871520620666200128112558
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prostate Cancer Radiotherapy on Testosterone Level: A Systematic Review and Meta-analysis

Abstract: Introduction: In the current study, a systematic search and meta-analysis were performed to evaluate the effect of prostate cancer radiotherapy on testosterone levels of patients. Methods: To illuminate the effect of radiotherapy on the testosterone level of prostate cancer patients, a systematic search was conducted in accordance with the PRISMA guideline in electronic databases of Scopus, Embase, PubMed, Web of Science, and clinical trials up to December 2018 using relevant keywords. Based on a certain se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…From daily fiducial image guidance, the testes-in-field mean dose was 3.50 Gy, whereas the testes-out-of-field scatter dose was 0.16 Gy for a complete IMRT course of 39 fractions. The authors concluded that incidental doses to the testes from prostate IMRT can be minimized by (1) opting to restrict the use of elective pelvic nodal fields, which would increase testicular dose to 1.72 Gy for 6 MV energies, (2) choosing photon energies less than 10 MV, and (3) using the smallest port sizes necessary for daily image guidance. 16 As such, each time IMRT needs to be performed, a computed tomography (CT) image is taken first to accurately locate the prostate for radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From daily fiducial image guidance, the testes-in-field mean dose was 3.50 Gy, whereas the testes-out-of-field scatter dose was 0.16 Gy for a complete IMRT course of 39 fractions. The authors concluded that incidental doses to the testes from prostate IMRT can be minimized by (1) opting to restrict the use of elective pelvic nodal fields, which would increase testicular dose to 1.72 Gy for 6 MV energies, (2) choosing photon energies less than 10 MV, and (3) using the smallest port sizes necessary for daily image guidance. 16 As such, each time IMRT needs to be performed, a computed tomography (CT) image is taken first to accurately locate the prostate for radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on external-beam radiation therapy (EBRT) have evaluated changes in serum testosterone levels in patients receiving EBRT for prostate cancer 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 and other pelvic malignancies. 10 , 11 NRG Oncology, a newly developed clinical trials network group consisting of the coordinated efforts of the National Surgical Adjuvant Breast and Bowel Project, the Radiation Therapy Oncology Group (RTOG), and the Gynecologic Oncology Group recently reported on the RTOG 9408 randomized clinical trial and found that a total dose of 68.4 Gy to the prostate was only associated with a median decrease in testosterone of 13.5% at 3 months after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] reported that secondary doses during prostate PT were ~10 −4 Sv Gy –1 at 50 cm from the beam isocenter and were an order of magnitude lower than during conventional IMRT. In addition, a systematic review and meta-analysis revealed a greater reduction in testosterone level after conventional radiotherapy and IMRT/SBRT than after PT [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 There are several therapeutic modalities for this malignancy including radical prostatectomy, radiotherapy and hormonal therapy. [2][3][4] It has been proven that different therapeutic techniques of external beam radiotherapy (EBRT) can be applied as a standard modality for prostate cancer treatment. 5,6 The main goal of three-dimensional conformal radiation therapy (3DCRT), as an EBRT technique, is to deliver conformal dose distribution to the target volume while minimising radiation dose to surrounding normal tissues.…”
Section: Introductionmentioning
confidence: 99%